Prophylactic use of interleukin 6 monoclonal antibody can reduce CRS response of CAR-T cell therapy - Dou, Baitao; Ren, Shihui; Qiu, Ling; Zhang, Xupai; Zhang, Nan; Cai, Jiao; Chen, Dan; Zhang, Qian; Yao, Hao; Fan, Fangyi (Frontiers in Medicine, 2024)
Background Chimeric antigen receptor T (CAR-T) cell immunotherapy is becoming one of the most promising treatments for hematological malignancies, however, complications such as cytokine release syndrome (CRS) seriously threaten the lives of patients. Interleukin 6(IL-6) monoclonal antibody is the common and useful treatment of CRS, however, it is not clear whether prophylactic use IL-6 monoclonal antibody before CAR-T therapy can reduce the incidence of CRS. Purpose This study aims to systematically evaluate whether the prophylactic use of IL-6 monoclonal antibody can reduce the incidence of CRS. Data sources and methods We searched the PubMed, Embase, web of Science, and Cochrane Library databases for studies that reported the prophylactic use of IL-6 monoclonal antibody in the treatment of CRS-related complications of CAR-T cell immunotherapy before December 2022. The literature is screened according to the established inclusion and exclusion criteria, relevant data are extracted, and the quality of the literature is evaluated using the scale Cochrane bias risk assessment tool, and the Review Manager 5.3 is used to draw for related charts. Since the two experimental data only provide the median, the maximum and minimum values of the data, the mean and standard (Standard Deviation, SD) are calculated by this document Delai, and finally use Review Manager for data processing, and STATA software for supplementation. Results A total of 2 trials with a total of 37 participants were included in this study. Meta-analysis showed that compared with no use of IL-6 monoclonal antibody to prevent CRS, IL-6 monoclonal antibody was given to patients at 8 mg/kg one hour before CAR-T cell infusion, which reduced the incidence of CRS [RR: 0.41 95% confidence interval (0.20, 0.86) I[2] = 0.0% P = 0.338 z = −2.369 (p = 0.018)]. In subgroup analysis, compared with those who did not use IL-6 monoclonal antibody to prevent CRS, IL-6 monoclonal antibody was given to patients at 8 mg/kg one hour before CAR-T cell infusion, which reduced lactate dehydrogenase (LDH)[MD: −617.21, 95% confidence interval (−1104.41, −130.01) I[2] = 0% P = 0.88 Z = 2.48 (P = 0.01)], prophylactic use of IL-6 monoclonal antibody has a significant effect on reducing peak C-reactive protein (CRP) after CAR-T therapy [MD: −11.58, 95% confidence interval (−15.28, −7.88) I[2] = 0.0% P = 0.73 z = 6.14 (p < 0.00001)]. Conclusion The prophylactic use of IL-6 monoclonal antibody can significantly reduce the incidence of CRS complications after CAR-T therapy, can also reduce LDH vaule and peak CRP vaule after CAR-T therapy. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023487662, identifier CRD42023487662.